MEKANISME LETTER OF CREDIT SYARIAH DI PT BANK BNI SYARIAH - Yutika, Meisa; Sa'diyah, Diah Siti (Al-Muamalat: Jurnal Ekonomi Syariah, 2018)
The existence of the changing times, demanding a State of international relations in order to support economic development. One form of international relations, namely business and international trade. one of the first in the international payment system is to use a letter of credit (LC) on the banking service product. LC Sharia is a product that is adopted from Conventional Banking products. However, until now, has not found the regulation governing implementation mechanisms explicitly Sharia LC in Indonesia. Therefore, the need for research on the mechanism of LC in the Islamic Penbankan In Indonesia. The purpose of this research was: 1) To compare the mechanism of implementation of the LC in Islamic banks and Conventional Banks, as well as looking for the difference between the two; 2) To know the regulations used in regulating Islamic Bank Sharia LC; 3) Mechanism to find out the views of the economic law of the Sharia (HES) against Sharia in LC mechanism Islamic banking in Indonesia.Â Â The framework of thought from this research that is using rule jurisprudence mu'amalah "a" meaning originally mu'amalah can be done until there is evidence again outlaw. If the mechanism of implementation of the LC in Conventional Banks is relatively the same as the mechanism of LC in Islamic banks, then the regulation mechanism of LC in Conventional Banks can be used as a regulatory mechanism of LC Sharia, as it is not contrary to the HES. Research methods used in this research is the juridical normative method, and using the conceptual approach and the approach of comparison. As for legal research in this unfamiliar term data but rather a source of law, After the legal materials collected the next step is to analyze the legal materials, described and meninjauanya from the viewpoint of HES, then pulled his conclusion. From the results of this research noted that basically the mechanism of implementation of the LC in Islamic banking in Indonesia (PT. Bank BNI Syariah) is not contrary to the HES. Although there has been no regulation which regulates clearly regarding the implementation of the Islamic Sharia and banking LC refers to the applicable regulation in banking Accounting i.e. UCP, but in practice there are some differences as in the Fund the arrears. Funds allocated for future delinquent Social Fund rather than to the operational funds of the bank, then it is not contrary to the HES.